Strategic roadmapping: theory and practice - Yee, Choy Leong (Universiti Putra Malaysia Press, 2013)
Strategic Roadmapping is an outstanding strategic planning tool for a company’s top-level management team to co-ordinate strategy, market, product, innovation, capability and resource. It incorporates the core concepts of strategic charting, visualization, technology road-mapping and resource-based view into practice. It is very useful tool, not oly for strategic planning, but for market, product, and technology planning. This book provides explanation and details the use of strategic roadmapping. It consists of an illustration of how to develop a strategic roadmap. The background and the underlying concept of strategic roadmapping are explained. The application examples from live industrial settings are provided. In addition, related research works that explore the theoretical foundation and practicality of strategic roadmapping are also included. It is not just an academic textbook but it is essentially a working document that provides useful guidelines to assist a company management team to use strategic roadmapping to perform their strategic planning tasks.